PENGARUH KOMPETENSI APARATUR, PARTISIPASI MASYARAKAT, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA : Studi Kasus Desa Di Kecamatan Wewaria Kabupaten Ende - Valentinus, Alexander; Ismail, Nuraini; Kapa, Sesilianus (Jurnal Riset Ilmu Akuntansi, 2021)
This research was conducted in a village in Wewaris District. Thepurpose of this study was to analyze the effect of apparatus competence, community participation and the use of information technology on management and village accountability ( a case study in the village of Wewaria District, Ende Regency). This type of research is a quantitative study with a sample of 50 respondents or village fund managers. The data of this study were collected through questionnaires, processed and analyzed using multiple regression analysis. The method used in determining the sample in this study was the purposive sampling technique. Pearson Correlation validity test and reliability test using Cronbach`s Alpha To test the hypothesis using the coefficient of determination test that has been adjusted to the F test, t test. The results of this research data indicate that the competence of the apparatus has a effect on the accountability of village fund management. Community participation has an effect on the accountability of village fund management. The use of information technology hasana effect on the accountability of village fund management.